Rhomboid protease inhibitors: Emerging tools and future therapeutics - Strisovsky, Kvido (Seminars in cell & developmental biology, 2016)
Rhomboid-family intramembrane serine proteases are evolutionarily widespread. Their functions in different organisms are gradually being uncovered and already suggest medical relevance for infectious diseases and cancer. In contrast to these advances, selective inhibitors that could serve as efficient tools for investigation of physiological functions of rhomboids, validation of their disease relevance or as templates for drug development are lacking. In this review I extract what is known about rhomboid protease mechanism and specificity, examine the currently used inhibitors, their mechanism of action and limitations, and conclude by proposing routes for future development of rhomboid protease inhibitors.
Keywords: Protease Inhibitors; vztahy mezi strukturou a aktivitou; substrátová specifita; Substrate specificity; Animals; Molecular Targeted Therapy; enzymatické testy; Inhibitor; inhibitory proteas; Humans; Enzyme Assays; Disease; Membrane Proteins; Substrate Specificity; cílená molekulární terapie; zvířata; membránové proteiny; Rhomboid protease; lidé; Structure-Activity Relationship; Mechanism